Rodzina miejscem spotkania i dialogu - Nowicki, Andrzej (Studia Edukacyjne, 2026)
The purpose of the article is to show the family as a unique place of encounter and dialogue. Achieving this goal first required drawing attention to dialogue, the fundamental tool of interpersonal communication. Hence the presentation of dialogue in its original meaning and structure, understood as a three-pronged semantic relation that takes into account the uniqueness of each element of this relation. An integral approach to the issue of dialogue also requires considering threats to its emergence and development. From the perspective of our reflections, several significant forms of these threats appear, such as exclusivism of views, misunderstanding, and superficial dialogue loneliness on the web. The conclusion of the article offers a proposal for dialogical coexistence within the family, understood as an opportunity to discover the meaning of two non-contradictory foundations of our human cognition and life decisions, namely reason and heart, which remain ever-relevant in our lives.